A Study of Mass Media Impact on Eating Disorder: A Path Analysis Study of The Mediator Variables of Social Comparison, Body Dissatisfaction, and Self-Esteem and The Mediator Variable of Body Image Self-Discrepancy - Laohapongphan, Shanaree; Blauw, Jon; Komolsevin, Rosechongporn (Scholar: Human Sciences, 2016)
This study aims to investigate a causal relationship between mass media exposure to thinness ideal, and eventually, leading to eating disorder. The participants are 1,064 female undergraduate students age between 18 – 23 years in Bangkok. Survey questionnaire is the key methodology for data gathering and apply Structural Equation Models (SEM) for statistical analysis. The study comprises 2 phases; phase 1 is a psychometric properties test of instrument translation for Comparison to Models Survey (CMS) and Eating Attitudes Test-26 (EAT-26), from English to Thai. The analysis of reliability, convergent validity, and discriminate validity showed good internal validity and its support to apply in Thai context. Phase 2 is designed to test a direct and indirect causal relationship between mass media impact and its influence on eating disorder, being mediated by social comparison, body dissatisfaction, and self-esteem. The path analysis of study model via SEM confirmed that mass media impact has both direct and indirect influence on eating disorder when mediated by those three mediators. Phase 3 is involved the level of self-discrepancy as a moderating factor to investigate its relationship between mass media impact and eating disorder.